Accounting Information System and Strategic Decision-Making in Islamic Education Management: A Qualitative Literature Review - Ani Safitri; Elystia Febriyanti; Muhammad Hendri Irawan; M. Zulfikar Sulkhi Aunillah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2026)
The advancement of information technology has transformed the role of information systems in education management, particularly in Islamic educational institutions. This study examines the relationship between Accounting Information Systems (AIS) and strategic decision-making through a qualitative literature review of 20 studies published between 2021 and 2025. The review focuses on the role of AIS in providing accurate financial information, its integration with Management Information Systems (MIS), and its contribution to efficiency, transparency, accountability, and data-driven decision-making. Findings indicate that integrated AIS and MIS enable leaders of madrasahs, pesantrens, and Islamic higher education institutions to formulate strategic policies more effectively while adhering to principles of good governance and sharia compliance. Digitalization through sharia financial applications, web-based systems, and AI-driven tools enhances reporting accuracy, planning, and policy evaluation. Key challenges include limited digital literacy, human resource competencies, and incomplete integration of system modules. The results underscore that AIS functions not merely as an administrative tool but as a strategic instrument promoting information-based management aligned with sharia values. This study offers both theoretical and practical implications for developing professional, transparent, and sustainable governance in Islamic educational institutions.